Comparison of the proximal chemical composition of the meat of Anadara tuberculosa and A. similis (Bivalvia: Arcidae) from Chomes, Puntarenas, Costa Rica - Cruz, Rafael A.; Fonseca-Rodríguez, Cristian; Chavarría-Solera, Fabián (Revista Ciencias Marinas y Costeras, 2012)
The seasonal variation in proximate biochemical composition and energy content of Anadara tuberculosa and A. similis were studied between March 2010 and February 2011 on a monthly basis. Fifteen to twenty individuals of each species were collected monthly. The proximate composition was determined following the methodology recommended by the Association of Official Analytical Chemists (AOAC). The average value of meat protein in A. similis was 57.9 ± 7.2%, carbohydrate 25.6 ± 4.4%, ash 6.87 ± 0.23%, and lipids 9.2 ± 0.2%. The average caloric content was 5.3 ± 0.2 kcal/g. For A. tuberculosa the values were protein 61.6%, carbohydrate 21.6%, ash 8.8%, and lipids 7.9%. The caloric value was 5.2 kcal/g. It can be concluded that both A. tuberculosa and A. similis have optimal nutritional value for human consumption, due to their low lipid and high protein contents.